Sistema de controle digital para WECS de eixo vertical - Almeida, Bruno Ricardo de (2012)
An option to minimize the energetic problems using renewable energy sources is the distributed micro generation in urban areas. In this kind of environment, where the winds are not regular ande turbulent, the efficiencies from vertical axis wind turbines are comparable to those ones from horizontal axis wind turbines, with the additional vantage of producing low mechanical vibrations at low rotation speeds. Thus, in order to explore this technology, this work presents a wind energy conversion system using a 1.5 kW vertical axis wind turbine. Firstly, a two power conversion stages topology is proposed, the first stage is a high frequency, semi controlled, three phase rectifier and the second stage is a classical Buck converter, the proposed topology is controlled by an analog control system. Secondly, in order to achieve size and efficiency improvements, a second topology is proposed, where the classic Buck converter is substituted by a synchronous, interleaved Buck converter, this second topology is fully digitally controlled. For both topologies, qualitative and quantitative analyses have been realized as well as its control systems have been design. Finally, simulation results are presented for both topologies, where an 18.5% input current total harmonic distortion can be verified for both topologies and, a 30% reduction of rms current trough dc link capacitors is verified for the second topology. A 1.5 kW prototype, based on the first proposed topology, was built and tested, achieving a full power efficiency of 91%.